2007
DOI: 10.1300/j198v05n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Indian Ocean Tsunami on the Well-Being of Children

Abstract: This article provides an overview of the plight of the "tsunami generation" detailing the social and physical conditions after the disaster. Children are most vulnerable and need protection and clear and sustained support for rehabilitation. The social psychological recovery and protection of children are key concerns of child welfare and internal social service organisations. Policy and programmes should build on the people's resilience and provide the psychosocial and community support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Details of each study and their special features were reported regarding authors, year, study type, vulnerable group, sample size, type of rehabilitation, setting and duration of rehabilitation, disaster type, and main concepts. The studies were mainly conducted in Asian countries and United States, including India, [15,19,20,[25][26][27]31] China, [18,22,23,34,36,37] Pakistan, [16,28,30] Iran, [13,17,21] Indonesia, [29,32] Sri Lanka [35] and United States. [14,24,33] The results of the studies showed that 56% of the studies are about rehabilitation programs for women, 32% is for children, 24% is for elderly, and 16% is for disabled people.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Details of each study and their special features were reported regarding authors, year, study type, vulnerable group, sample size, type of rehabilitation, setting and duration of rehabilitation, disaster type, and main concepts. The studies were mainly conducted in Asian countries and United States, including India, [15,19,20,[25][26][27]31] China, [18,22,23,34,36,37] Pakistan, [16,28,30] Iran, [13,17,21] Indonesia, [29,32] Sri Lanka [35] and United States. [14,24,33] The results of the studies showed that 56% of the studies are about rehabilitation programs for women, 32% is for children, 24% is for elderly, and 16% is for disabled people.…”
Section: Demographicsmentioning
confidence: 99%
“…[14,24,33] The results of the studies showed that 56% of the studies are about rehabilitation programs for women, 32% is for children, 24% is for elderly, and 16% is for disabled people. Each study included more than one [29] (2008) + --+ + -+ + + -6/10 Rathore et al [30] (2008) + --+ + --+ + + 6/10 Bazeghi et al [17] (2010) + ---+ --+ -+ 4/10 Ni et al [34] (2013) + + + ----+ + -5/10 Xiao et al [23] (2011) + -+ ---+ + --4/10 Li et al [22] (2012) + + -----+ + -4/10 Tan et al [25] ( [14] (2011) + + -----+ --3/10 Bazeghi et al [17] (2010) + ---+ --+ -+ 4/10 Mansoor et al [16] (2013) + + --+ -+ + + + 7/10 Larson et al [15] (2015) + + -+ + --+ -+ 6/10 Huang et al [18] [11,12] Abbreviations: yes (+), no (-); World J Emerg Med, Vol 8, No 4, 2017 vulnerable group. The mean of the period of physical, psychological, social, and economic rehabilitation programs was about 7.3 months varying from 1 week to 50 months, which were based on the type of the disaster and the countries where the disaster occurred.…”
Section: Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the tsunami, many of the approximately 13,000 newly orphaned children became institutionalized [25,26]. Many of which were trans-located to institutions far from their communities, despite having living family or community members with whom they might have stayed if that possibility had been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we would like to express our thanks to Sophia Buranakul and Wendy Firlotte in Krabi, the Prince of Songkhla University, to all our respondents and to the staff of government and non-government agencies and organisations who gave their time to talk to us and who so willingly spoke about an event that was traumatic for all and tragic for many. 2 For example, the 2004 Indian Ocean tsunami has led to papers on the tsunami and children (Ratrin Hestyanti, 2006;Tan, 2006); social work and the role of social workers (Busaspathumrong, 2006;Tang and Cheung, 2007); recovery and rehabilitation Rowlands et al, 2006); displacement (Rofi et al, 2006); volunteerism (Keong and Johnson Tan, 2006); civil society and disaster response (Srinivasan and Nagaraj, 2006); mental health issues (Nikapota, 2006;Vijayakumar et al, 2006); the economics of disaster (Nidhiprabha Bhanupong, 2006); charity and giving (Harrow et al, 2006;Williams, 2006); conflict (McGilvray, 2006); poverty (Purvis, 2005); gender (MacDonald, 2005;Felten-Biermann, 2006); religion (Silva, 2006); and on tourism and hotel management (Henderson, 2005). This list is, of course, growing all the time and does not include the many technical reports and studies undertaken by NGOs and multilateral agencies such as Oxfam and the UNDP (many of which can be freely downloaded).…”
Section: Notesmentioning
confidence: 99%